In silico Computational Analysis of Siddha Formulation Veppampoo Mathirai against Hypertension - Chitra , S. M. (Current Overview on Disease and Health Research Vol. 11, 2023)
The majority of people are affected with hypertension (HTN), the most prevalent non-communicable disease in the world. Despite the widespread availability of modern medications, people still express interest in using traditional medicine systems like Siddha to treat undesirable side effects. Through in silico computational study, Veppampoo mathirai, a polyherbal Siddha formulation, was examined for its potential impact on HTN. Through a literature review, the phytochemicals in the formulation were identified, picked out, and gathered. The AutoDock tool version 4 was used to carry out a molecular docking investigation. The target enzyme angiotensin-converting enzyme (ACE) was used to identify the lead compounds, which were then compared to generic captopril. Among the phytoprinciples analysed, Nimbiol and Gallic acid had ten interactions, whereas Piperic acid, Peperine, and Nimbolide had nine interactions which are higher than the standard Captopril. According to the results of the current investigation, the formulation Veppampoo mathirai may have potential binding effect against the ACE target enzyme, which lowers blood pressure.